MOTIVASI MAHASISWA SEKOLAH TINGGI TEOLOGI STAR’S LUB DALAM MEMILIH PROGRAM STUDI TEOLOGI - Rike Elmia Sitoki; Junni Yokiman; Leo Mardani Ruindungan (Institut Agama Kristen Negeri Kupang, 2023)
This study aims to determine the motivation of students to choose a theology study program. The research results will be useful for institutions administering theology study programs in designing new student recruitment strategies and developing the attractiveness of study programs. The subjects of this study were students of the theology study program at the Star's Lub Theology College Luwuk Banggai in Central Sulawesi. The method used is quantitative. Data was taken by questionnaire technique, measured by a Likert scale, and then analyzed using the SPSS application. The number of respondents who participated was 50 students in the 2022-2023 academic year. The results showed that the main motivation of the respondents was to realize their dream of becoming a priest. Decisions are taken personally, not parental decisions, and not the influence of friends. Respondents have also understood that a future career does not provide material guarantees. Respondents did not choose the theology study program because of limited choices and not because the cost was cheaper. From these findings, it can be concluded that respondents' motivation to choose the theology study program is very strong and very personal, with a willingness to serve.